Melatihkan Keterampilan Sosial Siswa Melalui Model Pembelajaran Kooperatif Tipe Numbered Head Together yang Mengintegrasikan Peer Assessment - Adawiyah, Siti Rabiatul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to develop learning tools that integrate peer assessment in a cooperative learning model of the numbered head together type to train students' social skills. The learning tools were developed using the Dick & Carey model. The learning tools developed were lesson plans, student books, student worksheets, learning outcome tests, and peer assessment sheets. The research data obtained were analyzed descriptively. The results showed that students' social skills for each meeting increased. Meanwhile, learning outcomes showed a significant increase compared to the values ​​obtained during the pre-test.